The Role of Communication in Promoting Solid Waste Management in Ghana - Tetteh, Jephthah M. (UniMAC-GIJ, 2020)
Waste has become a major challenge for many cities across the world. Due to the movement of large numbers of people to many developed parts of the world, waste generation capacities have increased. There is therefore the need to effectively address the problem before it deteriorates into another problem. At the heart of addressing these challenges is the use of communication. Communication brings people together to fight for a common course. It also ensures that people have valuable information that they can use to take major decisions that affect the management of waste in their communities. The study sought to establish how communication can be used to achieve these goals as well as examine the specific roles communication plays in the waste management process. The study recommends that waste management service providers must invest in communication and communication technologies in their bid to address the problem of waste in communities. They must be able to use creative means to bring people together in order to promote pro-environmental behaviour as well as make people owners and solutions to their local problems. This also means that peoples capacities must be built in order to effectively tackle the problem.
Thesis